How the Communal Buildings Created? Socio-Spatial Transformation of the Osing in Kemiren Village towards Social Sustainability - Dwiki Putrawan, I Made; Agusintadewi, Ni Ketut; Widiastuti, Widiastuti (University of Merdeka Malang, 2021)
The socio-cultural life of the Osing in Kemiren Village always interplays with their social activities and interactions, both among local people and travelers who come to visit the village. To accommodate these various activities, the Osing uses communal buildings, such as the Pesantogan Kemangi and two cultural houses: the Sukosari and the Osing. Data from the field reveals that the traditional house is a reference for creating communal buildings. The study aims to disclose the transformation process in spatial patterns and forms that occurs in communal facilities. It discusses a set of combination parts of traditional houses that create communal buildings. A qualitative inquiry was carried out the study with the ethnography approach. The result shows that socio-spatial transformation occurs in a dynamic change of communal activities that affect new architectural models of the public buildings. The transformation includes dimensional spatial patterns and building shapes, reduction, and additional spaces and components. Finally, the study contributes to being a reference for future research in the traditional architecture of the Osing. Both the local government and people work organized in preserving traditional architectural values as a pearl of local wisdom. Therefore, it supports and encourages tourism programs in Kemiren Village towards a socially sustainable community.